The Influence of Customer Participation Towards Repurchase Intention with Online Brand Community Trust and Positive eWOM as Intervening Variables in BeautyHaul - Profityas, Khairunnisa; Indrawati, Indrawati (International Journal of Science, Technology & Management, 2024)
E-commerce technology is advancing rapidly in Indonesia's personal care and cosmetics industries. BeautyHaul, the first personal care e-commerce company in Indonesia, aims to strengthen relationships with customers and increase their loyalty through consumer involvement in brand communities and word-of-mouth (eWOM) marketing which have the potential to increase repurchase intention. Data were collected from a sample survey of 155 respondents using purposive sampling method, which were analysed through Partial Least Squares-Structural Equation Modelling (PLS-SEM) and PLS-Predict. The coefficient of determination R2 indicates the influence of independent variables on repurchase intention is 44%. The analysis findings show that customer participation, positive electronic word-of-mouth (eWOM) and online brand community trust has positive and significant influence on repurchase intention on direct effect. The result shows that positive electronic word-of-mouth (eWOM) and online brand community trust also have positive and significant influence as mediators between customer participation and repurchase intention. Based on the findings of this study, BeautyHaul should concentrate more on boosting customer participation in order to strengthen repurchase intention.